Heinrich Uzel, the father of Thysanoptera studies - Fedor, Peter J.; Doričová, Martina; Prokop, Pavol; Mound, Laurence A. (Zootaxa, 2010)
Jindřich (Heinrich) Uzel, a Czech phytopathologist and entomologist, published in 1895 a monograph on the Order Thysanoptera that provided the basis for almost all subsequent work on this group of insects. Here we review all the papers and books on thrips that were published by Uzel, including relevant phytosanitary reports. A list is provided of 91 species-group taxa described in the 1895 monograph, together with their current status.